Organizational Culture as Determinant of Individual Perception of UTAUT Model: Case Study Credit Union in Indonesia - Indra Samsie; Titik Khawa Binti Abdul Rahman; Suarga Suarga (Journal of Information and Organizational Sciences)
This study aims to employ the Competitive Value Framework (CVF) and its value drivers as indicators for individual perceptions derived from the Unified Theory of Acceptance and Use Technology (UTAUT). The data was analyzed using the SEM-PLS method. The Reflective Formative Second Order Two-Stage Approach was used for the analysis, where variables related to organizational culture (OC) were examined using formative methods, while variables such as Performance Expectancy (PE), Social Influence (SI), Effort Expectancy (EE), and Behavioral Intention To Use (BI) were analyzed reflectively. The results revealed a significant correlation between OC and BI via EE and SI. However, the relationship between OC and BI via PE was found to be insignificant. This study contributes to theories about organizational culture, and information technology acceptance. On a practical level, these findings can assist decision-makers in paying greater attention to organizational culture when implementing new technologies.